Islamic Social Enterprise: A Systematic Literature Review of Models, Strategies, and Impacts - Wali Saputra (Journal of Literature Review, 2025)
This study presents a comprehensive Systematic Literature Review (SLR) exploring the evolving landscape of Islamic Social Enterprise (ISE)—a paradigm that unites Islamic economic principles with social entrepreneurship to advance both social and spiritual well-being. Drawing on 68 peer-reviewed studies published between 2010 and 2024 from databases such as Scopus, Web of Science, and ProQuest, this review systematically identifies and synthesizes the models, strategies, and impacts of ISE across diverse global contexts. The findings highlight four predominant models: zakat and sadaqah-based enterprises, productive waqf-based ventures, Islamic microfinance initiatives, and hybrid social–commercial organizations. Key implementation strategies include leveraging Islamic philanthropic instruments, fostering community-based empowerment, adopting digital innovations, and promoting sustainable management practices. ISE has demonstrated multifaceted impacts—ranging from poverty alleviation and financial inclusion to women’s empowerment and spiritual growth. However, challenges such as financial sustainability, governance weaknesses, and unclear regulatory frameworks continue to limit its broader scalability. The study’s novelty lies in proposing a multi-dimensional conceptual framework that integrates maqasid al-shariah, social enterprise theory, and sustainability principles—providing both theoretical enrichment and actionable insights for policymakers and practitioners. It further recommends a standardized impact measurement approach grounded in Islamic ethical values to enhance accountability and enable cross-regional comparison. Ultimately, ISE is positioned not merely as an adaptation of the Western social enterprise model but as a distinct paradigm that embodies a holistic vision of prosperity—encompassing material, social, and spiritual dimensions